MHD study of coronal waves: A numerical approach - Parhi, S.; Pandey, B. P.; Goossens, M.; Lakhina, G. S.; DeBruyne, P. (My University, 1997)
The solar corona, modelled by a low Î², resistive plasma slab sustains MHD wave propagations due to footpoint motions in the photosphere. The density, magnetic profile and driver are considered to be neither very smooth nor very steep. The numerical simulation presents the evolution of MHD waves and the formation of current sheet. Steep gradients in slow wave at the slab edges which are signature of resonance layer where dissipation takes place are observed. Singularity is removed by the inclusion of finite resistivity. Dissipation takes place around the resonance layer where the perturbation develops large gradients. The width of the resonance layer is calculated. The thickness of the AlfvÃ©n resonance layer is more than that of the slow wave resonance layer. Attempt is made to distinguish between slow and AlfvÃ©n wave resonance layers. Fast waves develop into kink modes. As plasma evolves the current sheets which provide the heating at the edges gets distorted and fragment into two current sheets at each edge which in turn come closer when the twist is enhanced.
Keywords: Coronal waves; Solar corona; MHD waves; Current sheet